Inflation, CPI, and Real Price Changes in Poland (specifically in Lubelskie Voivodship) in the Years 2002–2014 - Jarosław Bielak (Barometr Regionalny, 2015)
Inflation rate, Consumer Price Index, real price changes and the cost of living change perceived by people are sometimes reported to be significantly different. In this paper the analysis of these measures and goods and services price changes in Poland, in Lubelskie Voivodship in particular — in the years 2002–2014 — is conducted. The study is based on data published by Central Statistical Office of Poland and Narodowy Bank Polski . The results show a gap between officially published CPI and the inflation rate perceived by inhabitants who see inflation mainly from the angle of the prices of essential goods which they purchase every day.